The Effectiveness of Elbasir/Grazoprevir in Hepatitis C Patients with Stage 5 Chronic Kidney Disease (CKD) - Mustika, Syifa (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
ABSTRACTIntroduction: Treatment of hepatitis C in end stage renal disease patients  still a clinical challenge. Elbasvir/grazoprevir is a type of direct acting antiviral (DAA) drug used in treatment of Hepatitis C virus patients with renal disease. However, research on effectiveness of elbasvir/grazoprevir in hepatitis c virus patients with stage 5 chronic kidney disease (CKD) was limited. Therefore, this study aims to describe the effectiveness of elbasvir/grazoprevir on hepatitis C patients with stage 5 chronic kidney disease (CKD).Method: This research using analytic observational design with cross-sectional study approach. The effectiveness of elbasvir/grazoprevir in hepatitis C patients with stage 5 chronic kidney disease (CKD) were evaluated the viral load, SVR12, and kidney function. Data were obtained from medical records of hepatitis C patients at Hepatology Outpatient Clinic dr. Saiful Anwar hospital from January 1st 2021 until December 31st 2022. Data analysis used the chi-square test, paired t test, and the Wilcoxon test with a significance level of p0.05 and 95% confidence level.Results: This study obtained 52 respondents. Most of the patients after treatment elbasvir/grazoprevir had an SVR12 value of 94.23%. Creatinine levels significant increase from 122±40 mg/dl to 133.05±36.12 mg/dl (p=0,032). Urea levels significantly different from 12±3 mg/dl to 12.18±3.56 mg/dl (p=0,446).Conclusion: Elbasvir/grazoprevir was effective to treat hepatitis C patients with stage 5 CKD. Keywords: Hepatitis C, stage 5 CKD, effectiveness, elbasvir/grazoprevir